A REALIDADE DO GERENCIAMENTO DA ATIVIDADE LEITEIRA DA REGIÃO FRONTEIRA NOROESTE DO RIO GRANDE DO SUL - NÜSKE, ANA C.; SANTOR, CILIONE G.; ELGER, FABIO A.; GRIEBLER, GUSTAVO; EVANGELISTA, MARIO L. S.; HECKLER, VALM I. (Salão do Conhecimento, 2013)
Resumo